Drinking Trends of Adolescents in One Region of Korea - Park, Min-Hee (Advances in Social Sciences Research Journal, 2022)
This study examined the drinking conditions of adolescents in one region of South Korea. Data were collected online, and students from the fourth grade of elementary school to the third grade of high school participated. In this study, participants' 'drinking experience rate' was found to be 22.4%, ‘current drinking rate’ was 4.4%, and 'risk drinking rate' was 2.1%. In particular, the 'drinking experience rate' was 8.2% for elementary schools, 16.8% for middle schools, 28.4% for general high schools, and 38.9% for specialized vocational high schools. In addition, the annual trend showed a downward trend after 2019. Active support is needed to plan and implement alcohol-free health education and alcohol- prevention programs tailored to the drinking conditions of youth in the local community.